The Influence of Communication, Organizational Climate and Transformational Leadership Style of The Principal on Teacher Performance - Safrul Safrul (STAI Hubbulwathan Duri, 2022)
This study aims to determine whether organizational communication, climate and principals' transformational leadership affect teacher performance. This study uses a qualitative approach to the type of literature study. The data collection process was carried out using a literature study, meaning that the data collection process was carried out by reviewing several similar previous studies to produce new research results with several considerations. This method is a literature review from various sources and relevant references. From the results and discussion of this study, it can be concluded that good communication is needed in a school organization to facilitate and improve teacher performance and support from a comfortable and healthy organizational climate or environment also greatly affects teacher performance. Also, the principal's transformational leadership style becomes very important in improving teacher performance, because the principal is the leader and benchmark of a school organization.